People trafficking: prejudice and discrimination (Revista do Tribunal Regional Federal da 3ª Região, 2019)
To encourage reflection on sexual exploitation, prejudice and discrimination against transvestites associated with human trafficking and on public policies to tackle this type of crime are the objects of this article. For a better understanding of the subject, it was necessary to take a brief historical look at how the concept of homosexuality has been confused over time with that of transvestitism, as well as being associated with the practice of prostitution and marginalization. Thus, all homosexuals and transvestites who practiced and currently practice prostitution were and still are treated in São Paulo as a "police case", in other words, they must be controlled, disciplined and repressed in the name of maintaining order and good customs. Victims of prejudice, which continues to this day, transvestites are excluded from public policies, and are therefore on the margins of the social inclusion process, making them an easy target for recruitment by human trafficking networks. In this area, the challenges for Brazil are immense, especially for its most populous state, São Paulo, since the information and data obtained is inaccurate, insufficient and occasional. Although the issue is currently of interest to a greater number of organizations, including universities, in more than a decade, little progress has been made in terms of rigorous knowledge of practices, incorporating the issue into public agendas and, above all, evaluating and measuring the performance and impact of policies to combat human trafficking. Public authorities, universities and civil society are still unaware of the scale of the problem and its consequences for the country, without being able to define the best and most effective means of tackling it, according to local, regional or national contexts.
Keywords: human trafficking; homosexuals; transvestites; public policies; prejudice; discrimination